Information technology-based budget accountability at the University of Borneo Tarakan - Naufal, Putra Prima; Aisyah, Siti; Budiati, Ayunning (The International Journal of Politics and Sociology Research, 2023)
This research aims to describe Information Technology-Based Budget Accountability at the University of Borneo Tarakan (UBT) and analyze efforts to improve UBT Budget Accountability. This research uses a qualitative approach using observation, in-depth interviews, Focus Group Discussions (FGD), and documentation. Snowball sampling was used with three informants: Internal, Business Partners, and Beneficiaries. This research analyzes public accountability in government using Chandler and Plano dimensions: Fiscal accountability, Legal accountability, Program accountability, Process accountability, and Outcome accountability. The University of Borneo Tarakan (UBT) has various programs and activities that support the implementation of the Tri Dharma of Higher Education, including Education and Teaching, Research and Development, Community Service, Facilities and Infrastructure, and Operational Management Support. This operational support includes salaries, activity honorariums, official travel, and financing electricity and service subscriptions. The university implements budget accountability using the Agency Level Financial Application System (SAKTI) developed by the Ministry of Finance of the Republic of Indonesia. SAKTI operators adapt independently to application development. UBT is a State University (PTN) with Work Unit status whose budget planning, implementation, and financial reporting are regulated by the ministry. The university aims to realize good university governance through accountability aspects. In conclusion, Information Technology-based UBT Budget Accountability is good and strives to improve yearly.